Perbandingan Pertumbuhan dan Produksi Karotenoid pada Mikroalga Chlorella Vulgaris dan Chlorella Pyrenoidosa - Musifa, Eva (Journal of Natural Sciences, 2025)
Microalgae are a potential source of biological biomass due to their ability to produce various bioactive compounds. This study aims to analyze the growth curves and carotenoid content of two microalgae Chlorella Vulgaris and Chlorella Pyrenoidosa, to evaluate their potential as natural carotenoid sources. Microalgae cultures were cultivated in two different types of media, namely F1/2 Guillard and Walne. Growth monitoring was carried out by measuring dry biomass and cell density at a wavelength of 680 nm, while carotenoid content was analyzed spectrophotometrically at wavelengths of 470, 652, and 665 nm. All experiments were carried out in triplicate (n = 3) to obtain representative. The results showed that both species have distinctive growth patterns with different logarithmic phases. Chlorella Vulgaris showed a higher growth rate than Chlorella Pyrenoidosa, namely 0.80 ± 0.013 g/L and 0.43 ± 0.002 g/L for each microalgae. In addition, Guillard's F1/2 medium was proven to be more effective in supporting microalgae growth and carotenoid production in both microalgae strains, namely 0.653±0.018 µg/g for Chlorella Vulgaris and 0.436±0.049 µg/g for Chlorella Pyrenoidosa with a sig p value 0.05. These findings indicate that the selection of appropriate species and culture medium greatly influences microalgae productivity.